Starting Life with Hidden Wound: Bullying and Self-Reported Depression Symptoms among Early Adolescent in 3 Cities of Indonesia - Iwan Abdi Suandana; Anggriyani Wahyu Pinandari; Siswanto Agus Wilopo (Universitas Airlangga, 2024)
Background: Previous research revealed that bullying cause depression symptoms such as lack enthusiasm, anxious, being sensitive, and easily offended. Aims: This study aims to determine the relationship between bullying and self-reported depression in early adolescents using cross-sectional approach for Indonesia Global Early Adolescent Study data. Method: Depression symptom was collected using self-registered questionnaire about sadness, sleep disturbance, anxiety, and self-injury ideation from 4,684 students (2,207 boys and 2,477 girls). Logistic regressions were used to examine how bullying, and multilevel factors predict depression. Most adolescent aged 12-13 years old, living with complete parents, middle-up economic background, having hand-phone and using social media. Results: Adolescent reported experience at least 3 depression symptoms (60%), bullying (45%) and Adverse Childhood Experiences (ACEs; 70%). Result shows that boys (OR[CI];1.73[1.45,2.06]), having â‰¥5 ACEs (OR[CI];1.35[1.20,1.51]), living with relative (OR[CI];4.52[3.67,5.56]), spent more time with peers (OR[CI];1.52[1.33,1.73]), feeling unsafe (OR[CI];1.79[1.59,2.02]), having negative social-cohesion (OR[CI];1.50[1.34,1.67]) and high social-control (OR[CI];1.40[1.24,1.58]) are more likely to report depression. Conclusion: Multivariable analysis reveals significant association only on ACEs, time spent with peers, unsafe feeling, negative social-cohesion and high social-control. Bullying strongly predicts depression when adjusted by family and community variables only. Bullying prevention program should address other socialization agents such as peers, parents, teacher and community leader.